Politics of Value: New Approaches to Early Money and the State Proceedings of the 19th International Congress of Classical Archaeology - Heymans, Elon D.; Termeer, Marleen (Archaeology and Economy in the Ancient World, 2020)
As one of the most enduring icons of economic life, money has been a common feature and central focus in complex societies from Antiquity to the present. It gained weight as a key feature of Mediterranean economies in the course of the first millennium BCE, mostly in the form of coinage. But money is more than just coin, and its significance is more pervasive than just to the strict sphere of "the economy". In the ancient Mediterranean, money and its rise to prominence have been predominantly associated with the state. But can money only emerge under state authority? This volume questions the assumed relation between the spread of early forms of money and the state and draws attention to different ways in which money as an innovation could be anchored and socially embedded.